The political economy of migration enforcement: domestic versus border control - Facchini, Giovanni; Testa, Cecilia (Oxford University Press, 2015)
We study migration policy enforcement by an elected government. The policy-maker faces uncertainty on the supply of migrants, but has more information than the public on its preferences and the extent and effectiveness of its enforcement activities. We show that a utilitarian government preferring more migrants than the majority may find it optimal to set a restrictive target to please the median voter, while relaxing its enforcement to admit more foreigners in a concealed way. Lax enforcement may be achieved either by deploy- ing inadequate resources on cost–effective activities (domestic enforcement) or by allocating a larger budget on less effective tools (border enforcement). The attractiveness of one in- strument over the other depends on the size of the immigrant flow: if the supply is large, border enforcement might be preferred because, although more costly, it brings the number of migrants closer to the utilitarian optimum. Hence, re–election concerns might provide a rationale for the widespread use of less a effective enforcement tool, such as border control.